Keanekaragaman Semut (Hymenoptera: Formicidae)pada Beberapa Ketinggian di Taman Nasional Gunung Halimun Salak: Diversity of Ants (Hymenoptera: Formicidae) at Different Altitudes in Gunung Halimun Salak National Park - Irfani, Ewi; Haneda, Noor Farikhah (Jurnal Ilmu Ilmu Kehutanan, 2025)
The vegetation and wildlife of Gunung Halimun Salak National Park (GHSNP) are quite diverse. Ants (family: Formicidae) are among the diversity's less studied components. The hilly terrain of Gunung Halimun Salak National Park has not seen considerable alterationOne of the more fascinating aspects of studying wildlife is insects, particularly ants. Research on ants in the mountains at different elevations has been scarce up to this point. The purpose of this study is to examine the ant community at seven different elevations in terms of abundance, variety, and community similarity and to determine how ant diversity and environmental factors relate to one another. The soil arthropods were collected using pitfall traps, placed in several altitudes, i.e., 500 m, 700 m, 900 m, 1100 m, 1300 m, 1500 m, and 1700 m . Overall, 1536 ants were measured for abundance throughout all high-altitude habitats. At 700 m, the greatest number of arthropods (365 individuals) was found. There were just 85 ants at the maximum elevation of 1700 meters, which was the lowest ant abundance. The dominant morphospecies of the order Hymnoptera/ants (Formicidae) were Pheidole sp. and Polyarchis sp.